2014
DOI: 10.1093/inthealth/ihu076
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with risk behavior in travelers to tropical and subtropical regions

Abstract: 27Background: Recent decades have seen a rise in population movements and, therefore, 28 Results: 66% of travelers received pre-travel advice and 31% took malaria prophylaxis. 37At least one risk behavior was reported by 82.6% of travelers. People travelling for 1-6 38 months had a 3-fold higher likelihood of experiencing risk behaviors than people 39 travelling for <1 month (95%CI 1.54-5.81, p=0.001), and those travelling for >6 months 40 had a 13-fold higher likelihood (95%CI 3.11-56.14, p<0.001) compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…These results are in line with other studies on alcohol-related behavior of young people attending school leaving events or music festivals [33,34]. The use of alcohol during MGs does not only raise incidents rates of gatheringrelated injuries, but also the risk of becoming victim of robbery and brawls or acquiring sexually transmitted diseases (STDs) [35,36]. Risk behavior with respect to sexual contacts may be gender-or destination specific: While travelers to the FIFA world cup 2014 in Brazil had a higher rate of condom carriage, which was independently associated with alcohol consumption, and reported a significantly higher rate of sexual contacts outside of a relationship or the need for HIV testing after return, studies on STDs during the Olympic Games in London 2012 did not show increased attendances at sexual health services [37,38].…”
Section: Discussionsupporting
confidence: 88%
“…These results are in line with other studies on alcohol-related behavior of young people attending school leaving events or music festivals [33,34]. The use of alcohol during MGs does not only raise incidents rates of gatheringrelated injuries, but also the risk of becoming victim of robbery and brawls or acquiring sexually transmitted diseases (STDs) [35,36]. Risk behavior with respect to sexual contacts may be gender-or destination specific: While travelers to the FIFA world cup 2014 in Brazil had a higher rate of condom carriage, which was independently associated with alcohol consumption, and reported a significantly higher rate of sexual contacts outside of a relationship or the need for HIV testing after return, studies on STDs during the Olympic Games in London 2012 did not show increased attendances at sexual health services [37,38].…”
Section: Discussionsupporting
confidence: 88%
“…In regard to malaria, our study confirms and extends a recent review that found risk factors associated with malaria were “non-use or inappropriate use of chemoprophylaxis, age, delay in seeking care, incorrect treatment, delay in diagnosis, infection with Plasmodium falciparum , non-immunity, travelling as a tourist, and sex [ 36 ].” The case fatality rate ranged from 0.2% to 3%. Other researchers found younger travelers to be higher risk takers during traveling [ 37 ], where others found travelers older than 70 years of age at greatest risk of dying [ 38 ]. Clearly malaria chemoprophylaxis and counseling on risk avoidance of malaria are indicated for international travelers to endemic areas.…”
Section: Recommendationsmentioning
confidence: 99%
“…Much of this can be blamed on the temporary loss of situational awareness and loss of inhibition with a corresponding relaxed attitude toward safety. This may result in, for example, an increased likelihood to have unprotected sex (Croughs et al, 2008), consume excessive amounts of alcohol (Cabada et al, 2011), and not comply with travel medical advice (Aldea et al, 2015). International travelers suffer from many health problems while on holiday (Steffen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%